How can patient partnership help to improve equality as COVID‐19 moves from pandemic to endemic? - Natasha Treagust (Wiley, 2023)
Abstract One of the stated aims of the National Health Service (NHS) within its constitution is the promotion of equality. However, there is evidence inequality has increased over the last decade and the COVID‐19 pandemic has exacerbated this. The current pressures on healthcare mean that there is a case for a shift in approach as we transition to living with endemic COVID‐19. This article sets out how putting patient partnership front and centre at an individual, systems and national level has the potential to improve equality and assist the NHS in achieving its founding principles.